The Social and Psychological Impact of Women’s Empowerment in Child Education: Rethinking Motherhood - Hossain, Md. Sabbir; Chowdhury, Md. Mahmud Hasan (Universitas Negeri Semarang, 2023)
This paper exhibits new empirical evidence of women’s empowerment regarding child education. It examines the impacts of women's empowerment in social and psychological child education, focusing specifically on motherhood. It also criticizes the fragile bonding between mothers and children in respect of women’s empowerment. The researchers use descriptive research design and qualitative methods where they take interviews to get the expected output of the research from the selected population. The findings of this study present the handicaps of mothers that are engaged in jobs in terms of parenting. Most of the mothers opined that employed mothers can earn money which gives them a positive vibe but they fail to manage proper nourishment for their children to educate them properly. So their children face immense difficulties from social and psychological perspectives while unemployed mothers can manage sufficient time to nurture their children. Despite having some visible benefits of women’s empowerment the researchers mainly focus on the mental gap between children and employed mothers and the potential negative outcome of a mother-child mental gap from sociological and psychological perspectives.